O cinema mato-grossense : perspectivas do turismo cinematográfico - Carneiro, Licia Fassarella (2016)
This research proposes, through the study of concepts like fim induced tourism and place marketing, analyze Mato Grosso’s audiovisual market from the perspective of film induced tourism. The state of Mato Grosso does not have strategies that seek to promote the place through film or an audiovisual production system with national visibility. The research is based on an interdisciplinary context, linking the areas of economy, tourism and film and includes exploratory research, using the techniques of bibliographic and documentary research, as well as data collection and structured interview as means to build a theoretical framework on film induced tourism and on place marketing in Mato Grosso. At the end of the work, we intend to present an analysis of Mato Grosso’s audiovisual market and the outlook for the state so it can be incorporated into the targeted destinations for the practice of film induced tourism.